The Spiny Mouse—A Menstruating Rodent to Build a Bridge From Bench to Bedside - Bellofiore, Nadia; McKenna, Jarrod; Ellery, Stacey; Temple-Smith, Peter (Frontiers in Reproductive Health, 2021)
Menstruation, the cyclical breakdown of the uterine lining, is arguably one of evolution's most mysterious reproductive strategies. The complexity and rarity of menstruation within the animal kingdom is undoubtedly a leading contributor to our current lack of understanding about menstrual function and disorders. In particular, the molecular and environmental mechanisms that drive menstrual and fertility dysregulation remain ambiguous, owing to the restricted opportunities to study menstruation and model menstrual disorders in species outside the primates. The recent discovery of naturally occurring menstruation in the Egyptian spiny mouse (Acomys cahirinus) offers a new laboratory model with significant benefits for prospective research in women's health. This review summarises current knowledge of spiny mouse menstruation, with an emphasis on spiral artery formation, inflammation and endocrinology. We offer a new perspective on cycle variation in menstrual bleeding between individual animals, and propose that this is indicative of fertility success. We discuss how we can harness our knowledge of the unique physiology of the spiny mouse to better understand vascular remodelling and its implications for successful implantation, placentation, and foetal development. Our research suggests that the spiny mouse has the potential as a translational research model to bridge the gap between bench to bedside and provide improved reproductive health outcomes for women.